Developments, applications, and prospects of cryo‐electron microscopy. (26th December 2019) - Benjin, Xu; Ling, Liu
Abstract: Cryo‐electron microscopy (cryo‐EM) is a structural biological method that is used to determine the 3D structures of biomacromolecules. After years of development, cryo‐EM has made great achievements, which has led to a revolution in structural biology. In this article, the principle, characteristics, history, current situation, workflow, and common problems of cryo‐EM are systematically reviewed. In addition, the new development direction of cryo‐EM—cryo‐electron tomography (cryo‐ET), is discussed in detail. Also, cryo‐EM is prospected from the following aspects: the structural analysis of small proteins, the improvement of resolution and efficiency, and the relationship between cryo‐EM and drug development. This review is dedicated to giving readers a comprehensive understanding of the development and application of cryo‐EM, and to bringing them new insights.